Intranasal Immunization with Pneumococcal Polysaccharide Conjugate Vaccines Protects Mice against Invasive Pneumococcal Infections - Jakobsen, Håvard (American Society for Microbiology, 1999)
Host defenses against Streptococcus pneumoniae depend largely on opsonophagocytosis mediated by antibodies and complement. Since pneumococcus is a respiratory pathogen, mucosal immune responses may play a significant role in the defense against pneumococcal infections. Thus, mucosal vaccination may be an alternative approach to current immunization strategies, but effective adjuvants are required. Protein antigens induce significant mucosal immunoglobulin A (IgA) and systemic IgG responses when administered intranasally (i.n.) with the glyceride-polysorbate based adjuvant RhinoVax (RV) both in experimental animals and humans. The immunogenicity and efficacy of pneumococcal polysaccharide conjugate vaccines (PNC) of serotypes 1 and 3 was studied in mice after i.n. immunization with RV. Antibodies were measured in serum (IgM, IgG, and IgA) and saliva (IgA) and compared to antibody titers induced by parenteral immunization. The PNCs induced significant systemic IgG and IgA antibodies after i.n. immunization only when given with RV and, for serotype 1, serum IgG titers were comparable to titers induced by subcutaneous immunization. In addition, i.n. immunization with PNC-1 in RV elicited detectable mucosal IgA. These results demonstrate that RV is a potent mucosal adjuvant for polysaccharides conjugated to proteins. A majority of the PNC-1-immunized mice were protected against both bacteremia and pneumonia after i.n. challenge with a lethal dose of serotype 1 pneumococci, and protection correlated significantly with the serum IgG titers. Similarly, the survival of mice immunized i.n. with PNC-3 in RV was significantly prolonged. These results indicate that mucosal vaccination with PNC and adjuvants may be an alternative strategy for prevention against pneumococcal infections.